2016
DOI: 10.1108/lodj-09-2014-0178
|View full text |Cite
|
Sign up to set email alerts
|

Transformational leader attributes: interpersonal skills, engagement, and well-being

Abstract: Purpose – The purpose of this paper is to examine the effects of interpersonal skills (emotional and political skills) and work engagement on transformational leadership and leader well-being at work. Design/methodology/approach – Emotional control, emotional sensitivity, political skills, work engagement, transformational leadership behaviors, and job satisfaction were assessed in an empirical study of 278 employees. The relationships b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 74 publications
5
31
0
2
Order By: Relevance
“…Previous research has found that managers thought it was hard to ask for support from people they worked with, particularly when it was concerned with feeling stressed and exhausted or having too much to do [45,[51][52]. Maintaining an image of being a competent and able manager is important for being accepted as an authority, maintain the trust of the organization and for the managers to be able to carry out their work [53][54][55][56][57][58][59]. Managers' perceived threats to their image have been shown to have consequences for their willingness to propose changes to top managers [60][61][62].…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous research has found that managers thought it was hard to ask for support from people they worked with, particularly when it was concerned with feeling stressed and exhausted or having too much to do [45,[51][52]. Maintaining an image of being a competent and able manager is important for being accepted as an authority, maintain the trust of the organization and for the managers to be able to carry out their work [53][54][55][56][57][58][59]. Managers' perceived threats to their image have been shown to have consequences for their willingness to propose changes to top managers [60][61][62].…”
Section: Literature Reviewmentioning
confidence: 99%
“…This in turn allowed the managers to build or maintain their managerial image of being competent, which was important to maintain the confidence of the closest organization [e.g. [53][54][55][56][57][58][59].…”
Section: Work-related Support Is Sought From Sources Within the Workpmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, the immersion into work achieved by engagement is more holistic and all-encompassing than job involvement. For the politically oriented, such high engagement directed at "winning the game" is bound to be challenging, leading to heightened job satisfaction (Mencl, Wefald, & van Ittersum, 2016).…”
Section: Increasing Engagementmentioning
confidence: 99%